The Most Recent Advances and Uses of AI in Cybersecurity - Muhammad Ismaeel Khan; Aftab Arif; Ali Raza A Khan (CV. Multi Kreasi Media, 2024)
The incorporation of modern technology into cybersecurity measures has become imperative due to the growing sophistication and frequency of cyber threats. This review delves into the most recent developments and uses of artificial intelligence (AI) in cybersecurity, emphasizing how it may improve threat detection, automate responses, and give businesses useful insights. The conversation covers the present state of artificial intelligence applications, such as automated threat intelligence, natural language processing, and machine learning, and it uses case studies from a variety of industries, including retail, healthcare, and finance, to demonstrate how effective they are. Important implementation hurdles for AI, such as data privacy difficulties, ethical concerns, and the high rate of false positives, are also covered, highlighting the necessity for enterprises to carefully manage these challenges. In terms of the future, the analysis points to several interesting avenues for AI in cybersecurity, such as enhanced automation, better predictive capabilities, and integration with cutting-edge innovations like quantum computing, block chain, and the Internet of Things (IoT). The review emphasizes how AI has the ability to completely change cybersecurity procedures and emphasizes how crucial it is to solve ethical and practical issues in order to reap the full benefits of this technology. Organizations may improve their cybersecurity posture and effectively respond to a changing threat landscape by implementing AI-driven solutions and cultivating a culture of continuous learning and adaptation.